Heavy metal accumulation in Corchorus olitorius L. and Talinum fruticosurp (Jacq) Wild grown on soil from abandoned battery dump site in lle-lgbon, Oyo State, Nigeria (2017)
Plants are essential component of the natural ecosystems and terrestrial food chains. They have the potential to accumulate toxic metals when grown on such polluted soil, which could have negative health effects on man and livestock, if consumed. This study was conducted to evaluate the heavy metal accumulation in Corchorus olitorius and Talinum fruticosurp grown on soil from abandoned automobile battery dumpsite in lle-lgbon, Lagelu Local Government Area, Oyo State, Nigeria. Heavy metals (Pb, Cd, Mn, Fe and Ni) concentrations in the soil, and rool and shoot of Corchorus olitorius and Talinum fruticosurp were evaluated and the Transfer Factor (TF) of heavy metals in plants were determined. The experiment was laid out in a completely randomized design with four replicates. The treatments were battery polluted soil from lle-lgbon and soil (control) from Teaching and Research Farm, University of Ibadan, Nigeria. Seeds and stein cuttings of C. olitorius and T. fruticosurp. respectively were planted into 5 kg pot of polluted and control soils. Heavy metal concentrations of the soil, shoot and root were analysed in the laboratory. Heavy metal concentrations of polluted soil were: Pb (2928 mg/ kg), Cd (17.4 mg/kg), Mn (4482 mg/kg) and Fe (1877 mg/kg) as compared to the control: Pb (124 mg/kg). Cd (undetected), Mn (5368 mg/kg) and Fe (25.8 mg/kg). Heavy metals in the root and shoot samples of Corchorus olitorius and Talinum fruticosurp were Pb and Fe. Cadmium, Fe and Pb showed TF> I for both vegetables. The study concluded that vegetables planted around lle-lgbon have high concentrations of Pb and Fe. Even though Fe in the vegetables was below WHO permissible level of 425 mg/kg, Pb concentration (3.0 mg/kg) was beyond WHO/FAO permissible level